2021
DOI: 10.4081/jear.2021.9632
|View full text |Cite
|
Sign up to set email alerts
|

First comprehensive contribution to the knowledge of the lepidopteran fauna of Gioia Tauro Plain, South Italy (Lepidoptera)

Abstract: In this paper, we investigated for the first time on the composition of nocturnal Lepidoptera of the Gioia Tauro Plain, Calabria region (South Italy). The main goal was to acquire information on the biodiversity of this insect order in an area little investigated and subject to strong anthropic pressures. The study was carried out for one year in 4 sites characterized by different habitats. Sampling was carried out about twice a month through the use of UV-LED light traps. In total, 791 specimens belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The fauna of Gelechiidae of southern Italy is scarcely known as very few records are available (Costa, 1863;Parenti, 2000;Scalercio et al 2015;Baldizzone & Scalercio, 2018;Bonelli et al 2021). For the Calabria and Basilicata regions only 36 species of Gelechiidae are known so far, most of them only having been recorded in very recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fauna of Gelechiidae of southern Italy is scarcely known as very few records are available (Costa, 1863;Parenti, 2000;Scalercio et al 2015;Baldizzone & Scalercio, 2018;Bonelli et al 2021). For the Calabria and Basilicata regions only 36 species of Gelechiidae are known so far, most of them only having been recorded in very recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, Scalercio et al (2015) listed two species from the Sila Mountains, Huemer & Karsholt (2018) listed Megacraspedus lanceolellus (Zeller, 1850), and Baldizzone & Scalercio (2018) raised the total number of species to 35 thanks to one week of investigations in the Aspromonte Massif. Bonelli et al (2021) reported one more species for the Gioia Tauro Plain reaching a total of 36 species.…”
Section: Introductionmentioning
confidence: 99%